Frailty and the Burden of Concurrent and Incident Disability in Patients With Cirrhosis: A Prospective Cohort Study. Issue 1 (31st October 2019) - Lai, Jennifer C.; Dodge, Jennifer L.; McCulloch, Charles E.; Covinsky, Kenneth E.; Singer, Jonathan P.
Abstract : Frailty results from the chronic effects of malnutrition and muscle wasting in patients with cirrhosis. It is well‐established that frailty is strongly associated with mortality in this population. However, little is known of its relationship with physical disability, a critical patient‐centered outcome. Adults with cirrhosis underwent outpatient testing of frailty using the Liver Frailty Index (LFI) and disability using activities of daily living (ADL; range 0‐6) and Instrumental ADL (IADL; range 0‐8) scales at one center between 2012 and 2016. We used adjusted multilevel logistic mixed‐effects regression to test the association between frailty and current disability (impairment with ≥1 ADL or IADL) and incident disability at 6 months among those without baseline disability. Of the 983 participants, 20% were robust, 32% were less robust, 33% were prefrail, and 15% were frail; 587 (60%) had at least 1 assessment. The percentage of participants with at least 1 baseline ADL or IADL impairment was 28% and 37%, respectively. In adjusted regression models, each point LFI increase was associated with a 3.3 and 4.6 higher odds of current difficulty with at least 1 ADL and IADL ( P < 0.001 for each), respectively. Among participants without baseline disability, each point LFI increase was associated with a 2.6 and 1.7 higher odds of having difficulty with at least 1 ADL and IADL at 6 months, respectively. Conclusion: Frailty is strongly associated with concurrent and incident disability in patients with cirrhosis. In the clinic, the LFI can be used to identify those in greatest need for additional support/resources to maintain functional independence. In research settings, the LFI may help to identify an enriched population for clinical trials of interventions aimed at those most vulnerable to disability. Abstract : Frailty is strongly associated with concurrent and incident disability in patients with cirrhosis. In the clinic, the Liver Frailty Index can be used to identify those in greatest need for additional support/resources to maintain functional independence. In research settings, the Liver Frailty Index may help identify an enriched population for clinical trials of interventions aimed at those most vulnerable to disability.